CHIKUNGUNYA AND ZIKA VIRUSES : Global Emerging Health Threats - Higgs, Stephen; Vanlandingham, Dana L.; Powers, Ann (San Diego, United States : ELSEVIER, 2018)
Chikungunya and Zika Viruses: Global Emerging Health Threats is the go-to resource for both historical and current information on this important virus that is rapidly increasing its global range. Epidemics since 2005 have spread from Africa and Asia, and through Europe, and an ongoing epidemic has caused nearly two million cases in the Americas. It causes severe crippling arthritis, with symptoms lasting for months or years. As no vaccine or treatment is available, there is international interest in the virus, thus funding opportunities for research have dramatically increased. This book presents our understanding of the virus, bringing comprehensive knowledge in a single source.
Includes index.
Bibliography : pages 338-346.
Keywords: Chikungunya; Zika virus infection